Object-Synchronized TSN Reconfiguration Under Continuous Low-Latency Streaming - Dominik Stohrmann; Rolf Ernst (IEEE Open Journal of the Communications Society)
In-Vehicle Networks (IVN) are under intense pressure to be resource-efficient at low cost and flexible enough for the future. The deployment of a large number of new sensors for autonomous driving and self-awareness significantly increases the demand for network resources with low latency. In addition, the dynamics of network traffic lead to large over-provisioning of resources due to the lack of flexibility in statically designed networks. Application-aware resource management addresses these issues by providing information about transferred application data, enabling control of applications, and managing resource allocation during runtime. Application-level information is used to classify data transmissions into traffic groups based on their characteristics. By focusing on resource-intensive applications, such as large sensor object transmissions composed of hundreds of individual packets, it becomes possible to shift from packet-level to object-level deadlines. This shift introduces slack, enabling new opportunities for end-to-end IVN reconfiguration, which optimizes resource utilization and provides the flexibility to handle future demands. The generated slack is used to synchronize on one side the network access for object transmissions and on the other side the reconfiguration process. The combination of these two mechanisms enhances the efficiency of the timestamp-based reconfiguration approach. As a result, it is possible to reconfigure the network at runtime while ensuring lossless and seamless data transmission for high-bandwidth connections from the application’s perspective. To demonstrate the effectiveness of our protocol under real-world conditions, we implemented it on our hardware test setup using commercial off-the-shelf, Linux-based computers to build an IVN.